The Preadult Origins of Post-Materialism: A Longitudinal Sibling Study - Martin Kroh (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Using a research design that traces siblings preferences for postmaterialistic values in Germany over two decades, this paper provides new evidence on the origins of value preferences. Focusing on Inglehart's thesis of value change, we test the combined socialization and scarcity hypothesis against the social learning hypothesis, a prominent rival account of preadult value preference formation. Sibling estimates show that the shared preadult environment does indeed exert lasting effects on the permanent component of preferences for post-materialistic policies. In addition to weak effect of the shared experience of socioeconomic scarcity, we find that the intergenerational transmission of postmaterialism -which is disregarded by Inglehart's original thesis- plays a significant role in value preference acquisition. We discuss the implications of our individual-level findings for forecasts of aggregate-level trends in value change.
Keywords: 330